Papillary pattern in clear cell renal cell carcinoma: Clinicopathologic, morphologic, immunohistochemical and molecular genetic analysis of 23 cases - Alaghehbandan, Reza; Ulamec, Monika; Martinek, Petr; Pivovarcikova, Kristyna; Michalova, Kvetoslava; Skenderi, Faruk; Hora, Milan; Michal, Michal; Hes, Ondrej (Annals of diagnostic pathology, 2019)
Clear cell renal cell carcinoma (ccRCC), the most common histologic subtype of RCCs, demonstrates a wide spectrum of morphologic features (i.e., low-grade spindle cell, syncytial giant cells, and mucin-producing cells). However, papillary growth pattern in ccRCCs is rather a rare finding, which can present challenges in differential diagnostic work up. The aim of this study was to investigate ccRCCs with predominant papillary features from morphologic, immunohistochemical and molecular genetic perspectives. 23 clear cell renal cell carcinomas with papillary architecture were selected. Tumors were evaluated morphologically, immunohistochemically, and molecularly by next-generation sequencing (NGS). The diagnosis of MiT family translocation RCC was excluded by TFE3 immunohistochemistry. Mean age of patients was 65.2 years (range 42-81 years), and 19/23 were male. Tumor size ranged from 1.6 to 12.8 cm (median 6.5 cm). At a median follow-up of 2.5 years (range 1.5-9 years), 2 patients (8.7%) died of disease, 2 developed metastasis. Areas of papillary pattern accounted for approximately 40-100% of the tumor. CK7 was negative in non-papillary areas in majority of cases (20/23, 87%), and was only focally positive in 3/23 cases (13%). In papillary areas, AMACR was positive/focally positive in 17/23 (73.9%) cases and in the non-papillary areas it was positive/focally positive in 22/23 (95.6%) cases. CAIX was mainly negative in both non-papillary and papillary areas (15/23 [65%] and 16/23 [69.5%], respectively). Molecular analysis of 15 analyzable cases revealed the most frequently mutated gene to be VHL (in 9 cases), followed by PRBM1 (in 2 cases) and 29 other different mutations in various genes. Papillary growth pattern in ccRCC is not an uncommon situation. Papillary RCC with clear cells and MiT family (TFE3) translocation RCCs are the major differential diagnostic considerations in such scenarios. Our NGS molecular analysis supported classifying such tumors as a morphologic variant of ccRCC.
Keywords: nádory ledvin; Humans; lidé středního věku; mutační analýza DNA; Biomarkers, Tumor; Papillary pattern; Female; Aged; dospělí; senioři; lidé; papilární adenokarcinom; Immunohistochemistry; NGS; imunohistochemie; nádorové biomarkery; Adult; DNA Mutational Analysis; ženské pohlaví; Male; Middle Aged; Adenocarcinoma, Papillary; Aged, 80 and over; vysoce účinné nukleotidové sekvenování; karcinom z renálních buněk; High-Throughput Nucleotide Sequencing; senioři nad 80 let; Carcinoma, Renal Cell; mužské pohlaví; Kidney Neoplasms; Clear cell renal cell carcinoma